Implicit Association of Symmetry with Positive Valence, High Arousal and Simplicity. (August 2013) - Bertamini, Marco; Makin, Alexis; Rampone, Giulia
Symmetrical visual patterns are preferred to random patterns. Studies using the Implicit Association Test (IAT) have shown that symmetry is associated with positive valence words (e.g. love), and random with negative valence words (e.g. hate). Valence is an important aspect of emotion, but equally interesting is the relationship between the symmetry–random dimension and the dimensions of arousal and complexity. Possible links have long been discussed but empirical evidence is limited. Using a series of four IAT experiments, we report that participants implicitly associate symmetrical patterns with words high in arousal, and random patterns with low arousal. We also found that symmetrical patterns were associated with simple mathematic expressions, while random patterns were associated with complex expressions. No link was found for another aspect of mathematical complexity (smaller or larger numbers). This pattern of results shows that aesthetic responses to symmetry involve both positive valence and high arousal and that these emotional responses arise from the perceptual simplicity of symmetry, in line with the fluency account of aesthetics.